Pengembangan Aplikasi Pelaporan Keuangan Desa Berbasis Citizen Centric - Yoshua Omega Maurya; Fajar Pradana; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Based on UU No. 20 tahun 2018 Tentang Pengelolaan Keuangan Desa pasal 72 village government must inform village finance to public, then the village government must make publication about village finance every year, to achieve it Ngawi regency government make a reporting about village finance to citizen and Badan Pembangunan Masyarakat dan Desa (BAPPEMASDESA). Village finance reporting to citizen carried out using billboards. Billboards has problem such broken, rainy, information not seen at night and etc. Bilboards make citizen go to village government office or BAPPEMASDESA for make complain about disinformation about Village finance reporting. Village in Ngawi regency in 2018 no one reported about Perubahan APBDesa and Realisasi APBDesa to citizen and BAPPEMASDESA. Previous E-Government website were still oriented to the government, that making people not getting information that was actually needed by government. Based this problem government created a system which has the main features finance reporting village consisting of APBDesa, Perubahan APBDesa and Realisasi APBDesa to citizen and BAPPEMASDESA and citizen complains. The system is made based on citizen centric which is based on the perspective of the citizen. The research begins with conducting requirement enginnering and literature study about citizen centric. The results of the requirement engineering get 53 functional requirements and 2 non-functional requirement, after carrying out requirement engineering, go to design phased and implementation phased. System developed by many language consists PHP (Laravel Framework), Javascript, HTML, CSS and MYSQL database. Implementation is complete followed by unit testing, and validation testing. The results of the test produce 100% valid it means all requirement was success implemented.